Filipino adults' use of household furniture plaything during childhood - Dela Cruz, Danielle Marie V. (College of Home Economics, University of the Philippines Diliman, 2023)
The purpose of this study was to investigate the use of household furniture as playthings during childhood among selected Filipino adults and understand how it helped them learn more about themselves and their environment. This qualitative study employed semi-structured interview as its data collection method. Using purposive and snowball sampling methods, ten Filipino adults who grew up in the Philippines and had a history of playing with furniture in their childhood were chosen and individually interviewed via Zoom Meetings using an interview questionnaire. Thematic analysis was used to analyze the data. Findings show that the participants played with different household furniture such as sofas, beds, cabinets, chairs, tables, bar stools, bar counters, tumba-tumba, benches, and even a clothes rack. Participants said they were motivated to play with furniture due to its availability at home, their desire to engage in creative play, their lack of toys or boredom with their toys, and its ability to accommodate different types of pretend play. The participants engaged in many pretend plays where the setting is the home (e.g., bahay-bahayan, lutu-lutuan) or outside the home (eg, castle, fortress, shop, hotel, etc.) in which they performed various roles and activities connected to such settings. When using furniture as playthings, the participants said they considered attributes, mostly visual, such as sturdiness, size, material, features that mimic actual objects, and color. They also had other considerations such as comfort and safety, if the furniture fulfilled the criteria needed for the type of play, the adaptability of the furniture, its weight, and accessibility and convenience. Playing with furniture as children enabled participants to discover things about themselves and their environment or the world around them. Knowing that children may use furniture for play, furniture designers and manufacturers must ensure that they incorporate safety features and avoid features that may harm children when designing and manufacturing household furniture.